Design of glass artifacts through rapid prototyping and rapid tooling - Acácio Pereira (2006)
The actual competition environment characterized by fast variations and consumer's sharp necessity in aesthetic satisfaction demands a constant adaptation of the companies, at the development and production levels. The production of decorating glass parts by thermoforming, with three-dimensional shapes, demands expensive moulds. The complexity associated to the manufacture of these moulds by traditional methods represents a substantial aggravation in price and development time of the final product, makes their production not attractive. The present work presents adequate methodologies for glass artefacts production by thermoforming, which are based on rapid prototyping models and ceramic moulds hardened by a sol-gel reaction (indirect rapid tooling process). This technology allows the reduction in the time to market and opens new opportunities in the design of new and bold artefacts.